2006
DOI: 10.1016/j.jacc.2006.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Efficacy of Cardiac Resynchronization Therapy on Exercise Tolerance and Disease Progression

Abstract: Heart failure patients with ventricular conduction disturbance and permanent AF treated with CRT showed large and sustained long-term (up to 4 year) improvements of left ventricular function and functional capacity, similar to patients in SR, only if AVJ ablation was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(56 citation statements)
references
References 36 publications
4
47
0
5
Order By: Relevance
“…3 A sub-analysis of the CARE-HF trial showed that in patients with new onset of AF, CRT significantly improved patient outcomes compared with optimal medical therapy. 47 Interestingly, Gasparini et al 48 showed that in patients with permanent AF, the benefit observed with CRT was similar to that observed in sinus rhythm only in the sub-group of AF patients who underwent an atrio-ventricular node ablation and in whom biventricular pacing was applied at least 85% of time. Further large clinical trials specifically dedicated to this population are certainly warranted.…”
Section: Patients With Permanent Atrial Fibrillationmentioning
confidence: 83%
“…3 A sub-analysis of the CARE-HF trial showed that in patients with new onset of AF, CRT significantly improved patient outcomes compared with optimal medical therapy. 47 Interestingly, Gasparini et al 48 showed that in patients with permanent AF, the benefit observed with CRT was similar to that observed in sinus rhythm only in the sub-group of AF patients who underwent an atrio-ventricular node ablation and in whom biventricular pacing was applied at least 85% of time. Further large clinical trials specifically dedicated to this population are certainly warranted.…”
Section: Patients With Permanent Atrial Fibrillationmentioning
confidence: 83%
“…A recent prospective investigation that evaluated the role of atrioventricular junction ablation in patients with CRT devices and permanent atrial fibrillation demonstrated the potential benefit of this intervention. There were a significantly higher proportion of responders in the ablation group compared to those treated with CRT alone (68% vs. 18%) at 12 months [52]. Though AV nodal ablation is irreversible and usually causes dependence on proper pacemaker function for survival, such data support its consideration when atrial fibrillation is a limiting factor in the potential benefits a patient could derive from a CRT device.…”
Section: Consideration For Patients With Atrial Fibrillationmentioning
confidence: 85%
“…In summary, a lower mean heart rate is associated with better clinical and hemodynamic response to CRT. In atrial fibrillation patients, one study suggests that beneficial effects are more pronounced after AV node ablation [13].…”
Section: Original Articlementioning
confidence: 99%